Work-related symptoms among workers exposed to black tea dust - Agnieszka Lipińska-Ojrzanowska; Marta Wiszniewska; Diana Tymoszuk; Cezary Pałczyński; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2015)
Background: Tea may be classified as unfermented green, semi-fermented oolong and fermented black. All of these types are derived from Camellia sinensis, the Tea Plant, which contains the low molecular weight (LMW) agent Epigallocatechin gallate (EGCg), probably responsible for allergic reactions. The aim of our study was to asses the work-related allergic symptoms and IgE-mediated sensitivity among black tea packers. Material and Methods: Study groups comprised 26 black tea packers (group 1) and 20 office workers (group 2). A questionnaire, skin prick tests (SPTs) to common allergens and black tea, evaluation of specific IgE (asIgE) to Camellia sinensis and moulds, pre- and post-work-shift spirometry were performed. Results: At least 1 symptom suggesting allergic disease was reported by 85% of the tea packers and 60% of the office workers. The most frequent positive results of SPTs were obtained with moulds (8%). A small decline in FEV1 (forced expiratory volume in 1 s) after the work shift was observed among tea packers sensitized to moulds. Conclusions: Although specific sensitization to black tea was not observed in our study groups, cough and skin symptoms were significantly more frequently among the tea packers than in office workers. The irritant impact on the airways and the skin of tea dust and/or sensitization to moulds contaminating tea leaves are being suspected. Med Pr 2015;66(1):11-15